2015
DOI: 10.1515/jbcpp-2015-0055
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of the endocannabinoid system in the pathogenesis and treatment of kidney diseases

Abstract: Endocannabinoids (eCBs) are endogenous lipid ligands that bind to cannabinoid receptors that also mediate the effects of marijuana. The eCB system is comprised of eCBs, anandamide, and 2-arachidonoyl glycerol, their cannabinoid-1 and cannabinoid-2 receptors (CB 1 and CB 2 , respectively), and the enzymes involved in their biosynthesis and degradation. It is present in both the central nervous system and peripheral organs including the kidney. The current review focuses on the role of the eCB system in normal k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 97 publications
(151 reference statements)
0
48
0
Order By: Relevance
“…842). The healthy kidney contains high basal levels of endocannabinoids, but its expression of CB2 receptors, instead, is still controversial.…”
Section: Kidneysmentioning
confidence: 99%
“…842). The healthy kidney contains high basal levels of endocannabinoids, but its expression of CB2 receptors, instead, is still controversial.…”
Section: Kidneysmentioning
confidence: 99%
“…The endocannabinoid system is present in the kidney, where it is involved in various renal functions . Normally, CB1R activation regulates renal vascular hemodynamics and stimulates the transport of ions and proteins in different nephron compartments.…”
Section: Experimental Pharmacologymentioning
confidence: 99%
“…The endocannabinoid system (ECS) is comprised mainly of 2 membrane receptors (CB 1 R and CB 2 R) and their 2 major endogenous ligands, N‐arachidonoyl‐ethanolamine (anandamide or AEA) and 2‐arachidonoyl‐glycerol (2‐AG). In addition to its well‐documented role in obesity and its metabolic complications, the ECS has been implicated in the pathogenesis of CKD, including DN . Both CB 1 R and CB 2 R are expressed in the human and rodent kidney, particularly in mesangial cells, podocytes and proximal tubular cells .…”
Section: Introductionmentioning
confidence: 99%
“…Both CB 1 R and CB 2 R are expressed in the human and rodent kidney, particularly in mesangial cells, podocytes and proximal tubular cells . Enzymes responsible for the biosynthesis and degradation of endocannabinoids are also expressed in the kidney . We have previously reported that CB 1 R activation in podocytes mediates podocyte injury caused by hyperglycaemia and increased RAAS activity in a rat model of T2D .…”
Section: Introductionmentioning
confidence: 99%